Popeye Sign From Rupture Bisceps Brachii : A Case Report - Tesalonika, La Luna Dinada (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction : Biceps tendon rupture without trauma is rare. Most cases occur at the junction between the tendon and the labrum or at the bony attachment site. Advanced age, smoking, and corticosteroid use are common risk factors for tendon degeneration and tendinopathy. Case Report : A 68-year-old male from Java came in with abrupt discomfort and swelling in his right arm. After examining him and using ultrasound, we found that he had a ruptured biceps tendon. To treat this, we chose a conservative approach with physical therapy and non-steroidal anti-inflammatory drugs (NSAIDs). Initially, we applied ice, supportive bandages, and once the risk of bleeding decreased, we gave him NSAIDs and advised rest. After four weeks of treatment, the patient's condition improved. Conclusion : A case of total atraumatic rupture of the proximal biceps tendon is presented in this report. The significance of the